2013
DOI: 10.1007/s13365-013-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cerebral injury in the setting of chronic HIV infection and antiretroviral therapy

Abstract: Background Emerging evidence suggests that CNS injury and neurocognitive impairment persist in the setting of chronic HIV infection and combination antiretroviral therapy (CART). Yet whether neurological injury can progress in this setting remains uncertain. Methods Magnetic resonance spectroscopy, neurocognitive and clinical assessments were performed over two years in 226 HIV-infected individuals on stable CART, including 138 individuals who were neurocognitively asymptomatic (NA). Concentrations of N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 45 publications
3
62
0
2
Order By: Relevance
“…For instance, increased glucose uptake in striatum has been suggested as an early indicator of subclinical neurological involvement [66], but studies in antiretroviral-treated individuals with undetectable viral loads have found varying degrees of reduced glucose uptake in the medial frontal gyrus [67], and evidence for a small but consistent age-related reduction of glucose uptake in the anterior cingulate cortex, but not in other brain regions [68]. Likewise, creatine, choline, N- acetylaspartate, glutamate-containing and glutamine-containing compounds appear to show annual decreases in multiple brain regions of HIV-infected patients on stable cART [69,70]. Neurocognitive decline appears to be specifically associated with reduced glutamate and glutamine containing compounds in multiple brain regions including frontal white and grey matter, basal ganglia and parietal grey matter [69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, increased glucose uptake in striatum has been suggested as an early indicator of subclinical neurological involvement [66], but studies in antiretroviral-treated individuals with undetectable viral loads have found varying degrees of reduced glucose uptake in the medial frontal gyrus [67], and evidence for a small but consistent age-related reduction of glucose uptake in the anterior cingulate cortex, but not in other brain regions [68]. Likewise, creatine, choline, N- acetylaspartate, glutamate-containing and glutamine-containing compounds appear to show annual decreases in multiple brain regions of HIV-infected patients on stable cART [69,70]. Neurocognitive decline appears to be specifically associated with reduced glutamate and glutamine containing compounds in multiple brain regions including frontal white and grey matter, basal ganglia and parietal grey matter [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, creatine, choline, N- acetylaspartate, glutamate-containing and glutamine-containing compounds appear to show annual decreases in multiple brain regions of HIV-infected patients on stable cART [69,70]. Neurocognitive decline appears to be specifically associated with reduced glutamate and glutamine containing compounds in multiple brain regions including frontal white and grey matter, basal ganglia and parietal grey matter [69,70]. These disease associated decreases in glutamate and glutamine were correlated with deficits in executive function, motor and psychomotor speed, attention and working memory [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, most MRS studies have been cross-sectional and have primarily focused on specific regions of interest. Additional longitudinal studies that focus on HIV+ patients as they transition across different disease states are needed [29]. …”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…Glutamate transmission and metabolism are affected in many neurological diseases, including Alzheimer’s disease (Ferrarese et al , 2001), Parkinson’s disease (Plaitakis et al , 2010), amyotrophic lateral sclerosis, epilepsy (Eid et al , 2013a; Eid et al , 2013b), and HIV-1–associated neurocognitive disorders (Cohen et al , 2010; Gongvatana et al , 2013; Lentz et al , 2009). Whether glutamate levels in CSF or plasma represents a useful indicator of HIV-associated excitotoxicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%